Nitrifying Biomass and Kinetics in Carbon Removal-Nitrification Systems - Hall, Richard Eric (My University, 1981)
Although several dynamic models of the nitrification process have been developed in recent years, application of this work to full scale design and operation has been limited. This is primarily due to the difficulties associated with accurate estimation of the several kinetic parameters required in these models. An examination of the literature indicated that differences in system SRT (Solids Retention Time) and influent carbon to nitrogen ratio (C:N) contribute to the wide diversity in reported nitrifier kinetics. This dissertation examines the degree to which these effects may be quantified for a combined carbon removal - nitrification process.
A kinetic parameter, batch estimation technique was proposed which allows the measurement of nitrifier kinetics in the presence of heterotrophic microorganisms. The method utilizes a pure culture activity equivalent approach, and requires a specific nitrification inhibitor to differentiate between heterotrophic and autotrophic nitrogen dynamics measured in situ. This technique was found to give satisfactory results at several levels of nitrifier biomass fraction.
The parameter estimation technique was then applied to laboratory scale extended aeration plants operated at a number of SRT and influent C:N levels. Parameter values determined under these conditions were summarized by empirical regression equations to quantify the SRT and C:N effects. Arrhenius temperature coefficients for pure nitrifiers at several SRTs were also determined.
The equations relating SRT, C:N and temperature effects were then incorporated into a dynamic mechanistic model of the suspended growth carbon removal-nitrification process. Following verification against steady state and transient data from independent sources, it was concluded that the model adequately predicts mixed culture nitrification rates without prior parameter calibration.
Several simulation runs were then utilized to illustrate that previously observed C:N effects were the result of altered nitrifier kinetics. However, reported SRT effects could be attributed to autotrophic-heterotrophic population dynamics.
Keywords: Chemical Engineering; Chemical Engineering